Valuing unpaid care work in Bhutan - Jooyeoun Suh; Changa Dorji; Valerie Mercer-Blackman; Aimée Hampel-Milagrosa (Asian Development Bank (ADB), 2020)
A growing body of scholarly literature has attempted to measure and value unpaid care work in various countries, but perhaps only the government statistical agencies in the United States and the United Kingdom have seriously undertaken periodic and systematic measures of the time spent on unpaid work at the national level, and partially incorporated those values into their gross domestic product (GDP). One country that has been ahead of its time on aspects of societal welfare measurement is Bhutan, which produces the Gross National Happiness (GNH) Index. However, until the first GNH Survey, in 2008, Bhutan did not have any sense of the size and distribution of unpaid work, despite its strong societal norms about the value of volunteering and community work. This paper is the first to estimate the value of unpaid care work in Bhutan. It shows the pros and cons of various approaches and their equivalent measures of unpaid care work as a share of GDP. As with similar studies on the topic, this paper also finds that women spend more than twice as much time as men performing unpaid care work, regardless of their income, age, residency, or number of people in the household. The paper also provides recommendations for improving the measurement of unpaid care work in Bhutan.
Keywords: D13; J16; J22; J39; O53; 330; Bhutan; gender; labor productivity; measurement; time use; unpaid care work